English Vocabulary Achievement Through Telling Stories Using Pictures in Islamic Elementary School - Aminulloh Aminulloh; Asropi Safi'i; Muhammad Eka Rahman (Madrosatuna: Journal of Islamic Elementary School, 2019)
This reserch focuses on English vocabulary achievement through telling stories Using pictures. The general problem of this research is How far is the English vocabulary achievement through telling stories using pictures of the fifth year student of MIMA KH Siddiq Jember?". In this research the quantitative data was analyzed by using descriptive statistics. Based on the description from data analysis, the result of students’ English vocabulary achievement through telling stories was 76, 6. After consulting to the table score classification levels, the score lied in the interval of 66 to 75. This meant that the English vocabulary achievement by telling stories using pictures of the fifth year students of MIMA KH Siddiq Jember is enough. Since, the result of this research was enough; it is possible supported by the student's activity in learning English, the teaching learning process and the school facilities.